The Activity of Army Krajova Vilnius District Partisan Brigades - Balbus , Tomasz (Genocidas ir rezistencija, 2012)
Vilnius was one of the regional centres of the Polish anti-Soviet underground. Members of the Polish underground operating in Vilnius and Kaunas were gathered there. Throughout the occupation of the north-eastern fringes of the Second Polish Republic, Vilnius was the main centre of the Polish military and civilian (political) underground.